Comparative Analysis of Custom-Designed Soft Pneumatic Actuators for Human Thumb Movement in Post-Stroke Rehabilitation - Ritonga, Syahirul Alim; Herianto (Jurnal Inotera, 2023)
One of the most potential applications of soft actuator is as wearable medical devices for post-stroke rehabilitation as a field that requires high levels of safety and adaptability. Incorporating SPAs into such devices can provide a safer and more secure solution, ensuring controlled movements that do not pose a risk to patients. However, there is a research gap regarding the design considerations for soft actuators specifically targeting the human thumb, which exhibits distinct motion patterns compared to the other fingers. This paper addresses this gap by developing and evaluating custom-designed SPAs for the movement of the human thumb, with a focus on post-stroke rehabilitation. Three SPA models (M1, M2, and M3) were proposed, and their performance in replicating the twisting motion of the thumb was assessed. The SPAs were fabricated using 3D printing, and image processing software was utilized for measurement and analysis. The results showed that the M3 model, with two sections of chambers in different axes, exhibited the best performance in generating the desired twisting angle. Integration of the M3 model with four finger-shaped SPAs enabled successful grasping and picking-like movements. This research contributes to the advancement of soft actuators in wearable medical devices, particularly in post-stroke rehabilitation, and holds promise for enhancing patient recovery and quality of life.